Procedural efficiency measures: the implementation of witness litigation in labor litigation - Bustamante Maita, Sherly Tania (2023)
The collapse of the judicial system in Spain has led to an incessant search for procedural instruments that favor the resolution capacity of judges and magistrates. To this end, the Draft Law on Procedural Efficiency Measures of the Public Justice Service contemplates, among other aspects, the implementation in the social jurisdiction of the socalled witness lawsuit. This is a figure designed to expedite proceedings that are objectively identical, so that only one of them is processed. The rest of the proceedings are suspended until the resolution of the lawsuit that has served as a witness or guide. This paper analyzes the legal configuration of this mechanism, which is related to essential aspects of the labor process and the right to effective judicial protection.